2014
DOI: 10.1016/j.nicl.2014.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Localized abnormalities in the cingulum bundle in patients with schizophrenia: A Diffusion Tensor tractography study

Abstract: The cingulum bundle (CB) connects gray matter structures of the limbic system and as such has been implicated in the etiology of schizophrenia. There is growing evidence to suggest that the CB is actually comprised of a conglomeration of discrete sub-connections. The present study aimed to use Diffusion Tensor tractography to subdivide the CB into its constituent sub-connections, and to investigate the structural integrity of these sub-connections in patients with schizophrenia and matched healthy controls. Di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
36
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 49 publications
8
36
2
Order By: Relevance
“…This result is also consistent with the results of a recent study by Whitford et al (2014) who identified a significant negative correlation between patients’ score on the global Delusions scale of the SAPS and their FA in a sub-component of the cingulum bundle . The cingulum bundle connects the cingulate gyrus with several cerebral regions, including the premotor, prefrontal and parietal cortices, thalamus and hippocampus (Pandya et al, 1981).…”
Section: Discussionsupporting
confidence: 92%
“…This result is also consistent with the results of a recent study by Whitford et al (2014) who identified a significant negative correlation between patients’ score on the global Delusions scale of the SAPS and their FA in a sub-component of the cingulum bundle . The cingulum bundle connects the cingulate gyrus with several cerebral regions, including the premotor, prefrontal and parietal cortices, thalamus and hippocampus (Pandya et al, 1981).…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, Hubl et al (2004) demonstrated reduced anisotropy in the cingulate bundle in patients without AVH compared to patients who had experienced AVH, but this was restricted to the left hemisphere. In contrast, Whitford et al (2014) found a negative correlation of FA values in Subsection 4.1 of the right cingulum with the hallucination subscale of SAPS. This subsection of the cingulum projects into the rostral anterior cingulate gyrus and the caudal anterior cingulate gyrus.…”
Section: Anatomical Connectivitycontrasting
confidence: 69%
“…For both psychopathologies, cognitive empathy impairments have been previously highlighted (Montag et al, 2007;Shamay-Tsoory et al, 2007;Baron-Cohen et al, 2013;Smith et al, 2014) as well as abnormalities of the microstructural organization of the cingulate bundle (Pugliese et al, 2009;Travers et al, 2012;Reis Marques et al, 2014;Lener et al, 2014;Whitford et al, 2014). To the best of our knowledge, no work to date has been planned to directly rely empathy impairments in these pathologies with abnormal DTI parameters in the cingulum.…”
Section: Cognitive Empathy Cingulum and Default Mode Network Connectmentioning
confidence: 99%